Skin Autofluorescence Predicts Cardiovascular Mortality in Patients on Chronic Hemodialysis. Issue 5 (24th January 2014) - Kimura, Hiroshi; Tanaka, Kenichi; Kanno, Makoto; Watanabe, Kimio; Hayashi, Yoshimitsu; Asahi, Koichi; Suzuki, Hodaka; Sato, Keiji; Sakaue, Michiaki; Terawaki, Hiroyuki; Nakayama, Masaaki; Miyata, Toshio; et al.
Abstract Tissue accumulation of advanced glycation end products (AGE) is thought to contribute to the progression of cardiovascular disease (CVD). Skin autofluorescence, a non‐invasive measure of AGE accumulation using autofluorescence of the skin under ultraviolet light, has been reported to be an independent predictor of mortality associated with CVD in Caucasian patients on chronic hemodialysis. The aim of this study was to assess the predictive value of skin autofluorescence on all‐cause and cardiovascular mortality in non‐Caucasian (Japanese) patients on chronic hemodialysis. Baseline skin autofluorescence was measured with an autofluorescence reader in 128 non‐Caucasian (Japanese) patients on chronic hemodialysis. All‐cause and cardiovascular mortality was monitored prospectively during a period of 6 years. During the follow‐up period, 42 of the 128 patients died; 19 of those patients died of CVD. Skin autofluorescence did not have a significant effect on all‐cause mortality. However, age, carotid artery intima‐media thickness (IMT), serum albumin, high‐sensitivity C‐reactive protein (hsCRP), skin autofluorescence and pre‐existing CVD were significantly correlated with cardiovascular mortality. Multivariate Cox regression analysis showed skin autofluorescence (adjusted hazard ratio [HR] 3.97; 95% confidence interval [CI]1.67–9.43), serum albumin (adjusted HR 0.05; 95% CI 0.01–0.32), and hsCRP (adjusted HR 1.55; 95% CI 1.18–2.05) to be independent predictors of cardiovascular mortality. The present study suggests that skin autofluorescence is an independent predictor of cardiovascular mortality in non‐Caucasian (Japanese) patients on chronic hemodialysis.